Peran Orang Tua dalam Meningkatkan Motivasi Belajar Anak Dengan Sistem Daring pada Masa Pandemi di Desa Depokrejo, Kebumen - Arifia Sabila Hayati (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2020)
This research is motivated by the results of observations and research as one of the Depokrejo village communities. This is to find out how the role of parents in developing learning abilities for early childhood during the Covid-19 pandemic. The subjects of this study were parents and their children. In this study, researchers used data collection methods in the form of interviews. The results of research on the role of parents teaching children in the midst of the Covid-19 pandemic, show that there are parents who pay less attention to children's learning activities at home and are busy with their respective jobs, but there are also parents who want to direct their children to study at home and mutually communicate and guide children to learn together. The conclusion of this study is that the role of parents who have high enthusiasm for learning motivation and developing children's learning abilities will have a good impact on children, especially in the current Covid-19 pandemic, children really need the role of parents to foster interest in learning. them through learning that will be taught at home.